Deep Time Ecstasy: Ponderings from Beyond the Time-Wall, Courtesy of Peter Sloterdijk - Andersson, Daniel (Cosmos and History: The Journal of Natural and Social Philosophy, 2022)
Review essay of Infinite Mobilization, by Peter Sloterdijk, translated by Sandra Berjan, Cambridge, Polity, 2020, 240 pp., 24.95, ISBN: 978-1-509-51847-0.